2002
DOI: 10.1007/s00787-002-0248-4
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural assessment of childhood temperament

Abstract: The Emotionality Activity Sociability (EAS) questionnaire focuses on heritable individual differences in reactivity and behavior which are often referred to in developmental temperament research. Psychometric properties of the French version of EAS were examined in a sample of 197 school-children aged six to 12 years. Parents, teachers and children aged nine years and more completed parallel forms of the EAS questionnaire. Confirmatory factor analysis was used to examine the fit between the original factors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Several studies provided support for the reliability and validity of the EAS questionnaire among children (e.g. Boer & Westenberg, 1994;Gasman et al, 2002). In the present study the internal consistency indicated relatively low, but acceptable, values of reliability for all dimensions (α = 0.78 for emotionality; α = 0.64 for activity; α = 0.71 for sociability; and α = 0.67 for shyness).…”
Section: Methodssupporting
confidence: 69%
“…Several studies provided support for the reliability and validity of the EAS questionnaire among children (e.g. Boer & Westenberg, 1994;Gasman et al, 2002). In the present study the internal consistency indicated relatively low, but acceptable, values of reliability for all dimensions (α = 0.78 for emotionality; α = 0.64 for activity; α = 0.71 for sociability; and α = 0.67 for shyness).…”
Section: Methodssupporting
confidence: 69%
“…In order to keep the response burden on participants as low as possible, the three most suitable items for this study out of five from the activity scale, a measure of vigor and tempo, were picked: (1) My child is always on the go; (2) My child is very energetic; and (3) My child prefers quiet, inactive games to more active ones (reversed). The psychometric properties have been examined in both European and north European contexts, displaying good psychometric properties [ 23 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The scores from the questions belonging to each temperament are summed to form the four temperament dimensions. The EAS has satisfactory psychometric properties in children and infants and has been validated in France [ 45 ]. In the current sample, reliability was satisfactory with moderate-to-high internal consistency (Cronbach alphas = 0.63−0.72) for the different dimensions.…”
Section: Methodsmentioning
confidence: 99%